Traffic-related air pollution (TRAP) exposure, lung function, airway inflammation and expiratory microbiota: A randomized crossover study - Rongrong Xu; Yanping Zhang; Tingting Wu; Hao Liu; Jianhao Peng; Zhanshan Wang; Te Ba; Baorong Zhang; Zhigang Li; Yongjie Wei (Ecotoxicology and Environmental Safety)
Traffic-related air pollution (TRAP) has been linked with numerous respiratory diseases. Recently, lung microbiome is proposed to be characterized with development and progression of respiratory diseases. However, the underlying effects of TRAP exposure on lung microbiome are rarely explored. We conducted a randomized, crossover study among 35 healthy adults, who participated in 2-h exposure treatments in the road or park scenario alternately, to investigate the impact of short-term TRAP exposure on expiratory health. Particle matters (PMs), nitrogen dioxide (NO2), carbon monoxide (CO) and volatile organic compounds (VOCs), lung function, fractional exhaled nitric oxide (FeNO) and lung microbiota were measured. We applied linear mixed-effect models to explore the associations. TRAP including NO2 and CO in the road were about 1.5 times higher than that in the park except for PMs, and total VOCs also showed higher concentrations. We observed elevated difference in FeNO was associated with high TRAP exposure in the road session, but didn’t find obvious changes in lung function. The abundance of Lentilactobacillus and Haepmophilus were distinct in the two groups, with significant correlations with changes to PEF and FeNO, respectively. Enrichment pathways related to transcription, amino acid and carbohydrate metabolism were altered following high TRAP exposure, suggesting TRAP contributed to the respiratory disease by changing metabolism of lung microbes. Our findings reveal VOCs in the road are another key air pollutant and provide novel mechanism for the respiratory effects of TRAP from the perspective of microbiome.